Manajemen Mutu Pendidikan Anak Usia Dini Wijaya Kusuma Rejang Lebong - Yanto, Murni (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2020)
This study aimed to discribe the application of management of Early Childoon Education in Wijaya Kusuma, jalan Suprapto, Talang Rimbo Baru, Curup Tengah District, Rejang Lebong Regency, Bengkulu. This tyfe of research is a qualitatifve descriptive study by taking a teacher at the wijaya Ealy Childhood Education Park Kusuma as the object of research. The data collection technique was carried out using structured interviews. The results showed that the Wijaya Kusuma Early Childhood Education Park had met management standards, namely (a) Planning, all institutational activities concerning what to do,where to do it,when it will be done, (b) Organization,planned to be compeleted by members of the work group, determining the work relationship between them and providing the appropriate work environment. (c) Direction,is the encouragement that will provide motivation in an organization. (d) Supervision to determine the realization of personnel behavior in educational organizations and whether theÂ level of attainment of educational goals is as desired. Supervision is carried out to collect data on the implementation of cooperation between tearhers, principals, counselors. (e) The quality of services provided to steakholders consisting of students, alumni and old school student.